Combined Mutagenesis and Kinetics Characterization of the Bilin‐Binding GAF Domain of the Protein Slr1393 from the Cyanobacterium Synechocystis PCC6803. Issue 8 (24th April 2014) - Xu, Xiu‐Ling; Gutt, Alexander; Mechelke, Jonas; Raffelberg, Sarah; Tang, Kun; Miao, Dan; Valle, Lorena; Borsarelli, Claudio D.; Zhao, Kai‐Hong; Gärtner, Wolfgang
Abstract The gene slr1393 from Synechocystis sp. PCC6803 encodes a protein composed of three GAF domains, a PAS domain, and a histidine kinase domain. GAF3 is the sole domain able to bind phycocyanobilin (PCB) as chromophore and to accomplish photochemistry: switching between a red‐absorbing parental and a green‐absorbing photoproduct state (λmax=649 and 536 nm, respectively). Conversions in both directions were followed by time‐resolved absorption spectroscopy with the separately expressed GAF3 domain of Slr1393. Global fit analysis of the recorded absorbance changes yielded three lifetimes (3.2 μs, 390 μs, and 1.5 ms) for the red‐to‐green conversion, and 1.2 μs, 340 μs, and 1 ms for the green‐to‐red conversion. In addition to the wild‐type (WT) protein, 24 mutated proteins were studied spectroscopically. The design of these site‐directed mutations was based on sequence alignments with related proteins and by employing the crystal structure of AnPixJg2 (PDB ID: 3W2Z), a Slr1393 orthologous from Anabaena sp. PCC7120. The structure of AnPixJg2 was also used as template for model building, thus confirming the strong structural similarity between the proteins, and for identifying amino acids to target for mutagenesis. Only amino acids in close proximity to the chromophore were exchanged, as these were considered likely to have an impact on the spectral and dynamic properties. Three groups of mutants were found: some showed absorption features similar to the WT protein, a second group showed modified absorbance properties, and the third group had lost the ability to bind the chromophore. The most unexpected result was obtained for the exchange at residue 532 (N532Y). In vivo assembly yielded a red‐absorbing, WT‐like protein. Irradiation, however, not only converted it into the green‐absorbing form, but also produced a 660 nm, further‐red‐shifted absorbance band. This photoproduct was fully reversible to the parental form upon green light irradiation.